X-RAY FLUORESCENCE SPECTROSCOPY IN MUSEUM PRACTICE: INVESTIGATION AND CONSERVATION OF ARTWORKS - Khurshid Tashpulatov,; Kosimova Fariza, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation:  This  article  analyzes  the  importance  of  X-ray  fluorescence spectroscopy (XRF) in museum practice for the study and conservation of works of art. XRF is an advanced method that allows for the non-invasive detection of pigments, metal elements, and other chemical components, and is an important tool for verifying the authenticity of works of art, planning restoration, and conservation processes. The article discusses the application of XRF technology in museum practice, the impact of pigment identification, metal content study, and conservation processes. This research will help protect works of art and allow museum conservators to make scientifically sound decisions.